Intraindividual Comparison Between [18F] PSMA-1007 PET/CT and Multiparametric MRI for Radiotherapy Planning in Primary Prostate Cancer Patients - Marinescu, Ioana M.; Spohn, Simon K. B.; Kiefer, Selina; Bronsert, Peter; Ceci, Lara; Holzschuh, Julius; Sigle, August; Jilg, Cordula A.; Rühle, Alexander; Sprave, Tanja; Nicolay, Nils H.; Winzer, Robert; et al. (Frontiers in Oncology, 2022)
Introduction Accurate detection and segmentation of the intraprostatic gross tumor volume (GTV) is pivotal for radiotherapy (RT) in primary prostate cancer (PCa) since it influences focal therapy target volumes and the patients’ cT stage. The study aimed to compare the performance of multiparametric resonance imaging (mpMRI) with [18F] PSMA-1007 positron emission tomography (PET) for intraprostatic GTV detection as well as delineation and to evaluate their respective influence on RT concepts. Materials and Methods In total, 93 patients from two German University Hospitals with [18F] PSMA-1007-PET/CT and MRI (Freiburg) or [18F] PSMA-1007-PET/MRI (Dresden) were retrospectively enrolled. Validated contouring techniques were applied for GTV-PET and -MRI segmentation. Absolute tumor volume and cT status were determined for each imaging method. PCa distribution from histopathological reports based on biopsy cores and surgery specimen were used as reference, in terms of laterality (uni- vs. bilateral). Results In the Freiburg cohort (n=84) mpMRI and PET detected in median 2 (range: 1-5) and 3 (range: 1-8) GTVs, respectively (p<0.01). The median GTV-MRI was significantly smaller than the GTV-PET measuring 2.05 vs 3.65 ml (p=0.0005). PET had a statistically significant higher concordance in laterality with surgery specimen compared to mpMRI (p=0.04) and biopsy (p<0.01), respectively. PSMA PET led to more cT2c and cT3b stages whereas cT3a stage was more pronounced in mpMRI. Based on the cT stage derived from mpMRI and PET information 21 and 23 and, 59 and 60 patients were intermediate- and high-risk according to NCCNv1.2022 criteria. In the Dresden cohort (n=9), similar results were observed. Conclusion Intraprostatic GTV segmentation based on [18F] PSMA-1007 PET results in more and larger GTVs compared to mpMRI This influences focal RT target volumes and cT stage definition but not the NCCN risk group.